SISTEM INFORMASI PEMINJAMAN DAN PENGEMBALIAN DOKUMEN REKAM MEDIS MENGGUNAKAN METODE WATERFALL (STUDI KASUS PUSKESMAS BANJARSENGON) - Nur Malika Jamil; Niyalatul Muna; Rossalina Adi Wijayanti; Andri Permana Wicaksono (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
The information system is made based on problems in recording the implementation of loans, returningmedical records. This computerized information system where in the borrowing and returning of medicalrecords is no longer manual. The purpose of this information system is to facilitate officers in recording,borrowing, returning, controlling and controlling medical records. The borrowing and return of medical recordsmust be controlled properly to reduce duplication of medical record numbers and delays in medical recorddocuments. Qualitative research using documentation data collection methods and interviews at theBanjarsengon Health Center in Jember. The method used in this research is the 2011 somerviel waterfallmethod. The steps taken are requirements analysis, system design, program code writing, and programtesting. The design of this information system uses flowchart design, context diagrams, Data Flow Diagrams(DFD), and Entity Relationship Diagrams (ERD) then the design results are implemented into a visual basicprogramming language using Miscrosoft Visual Studio 2010. The results of this study are lending informationsystems. and return of medical record documents. This information system is equipped with a warning alert asa notification that medical record documents borrowed by POLI to be returned immediately, can help ease theworkload of filing officers by minimizing the number of delays in medical record documents and duplication ofmedical record documents.